DESAIN DAN UJI COBA MEDIA PEMBELAJARAN MENGGUNAKAN MULTIMEDIA INTERAKTIF LECTORA INSPIRE PADA MATERI LARUTAN PENYANGGA - Aisyah, Siti; Fatisa, Yuni (Journal of Chemistry Education and Integration, 2022)
Abstract This research aimed at developing learning media using Lectora Ispire interactive multimedia on Buffer Solution lesson and knowing the levels of validity, practicality, and student response to the learning media developed. It was a Research and Development (R&D) with Luther development model that was limited to the fifth steptesting. This research was administered at State Senior High School 9 Pekanbaru. The subjects of this research were the lecturers, Chemistry subject teachers, and students. The object was learning media using Lectora Ispire interactive multimedia on Buffer Solution lesson. Validation test questionnaire, practicality test questionnaire, student response test, and interview were the techniques of collecting the data. The data obtained then were analyzed by using qualitative and quantitative descriptive analysis techniques. The research findings showed that the media validity level was 90.5% with very valid criterion, the practicality level was 94.17% with very practical criterion, and student response to the learning media was 91.6% with very good criterion. Based on this research, it could be concluded that learning media using Lectora Ispire interactive multimedia on Buffer Solution lesson was very valid and practical, so it was proper to be used as learning media at school. Keywords : Learning Media, Lectora Inspire, Buffer Solution